Safety and Efficacy of a Phage, kpssk3, in an in vivo Model of Carbapenem-Resistant Hypermucoviscous Klebsiella pneumoniae Bacteremia - Shi, Yunlong; Peng, Yuan; Zhang, Yixin; Chen, Yu; Zhang, Cheng; Luo, Xiaoqiang; Chen, Yajie; Yuan, Zhiqiang; Chen, Jing; Gong, Yali (Frontiers in Microbiology, 2021)
Antimicrobial resistance (AMR) is one of the most significant threats to global public health. As antibiotic failure is increasing, phages are gradually becoming important agents in the post-antibiotic era. In this study, the therapeutic effects and safety of kpssk3, a previously isolated phage infecting carbapenem-resistant hypermucoviscous Klebsiella pneumoniae (CR-HMKP), were evaluated in a mouse model of systemic CR-HMKP infection. The therapeutic efficacy experiment showed that intraperitoneal injection with a single dose of phage kpssk3 (1 × 107 PFU/mouse) 3 h post infection protected 100% of BALB/c mice against bacteremia induced by intraperitoneal challenge with a 2 × LD100 dose of NY03, a CR-HMKP clinical isolate. In addition, mice were treated with antibiotics from three classes (polymyxin B, tigecycline, and ceftazidime/avibactam plus aztreonam), and the 7 days survival rates of the treated mice were 20, 20, and 90%, respectively. The safety test consisted of 2 parts: determining the cytotoxicity of kpssk3 and evaluating the short- and long-term impacts of phage therapy on the mouse gut microbiota. Phage kpssk3 was shown to not be cytotoxic to mammalian cells in vitro or in vivo. Fecal samples were collected from the phage-treated mice at 3 time points before (0 day) and after (3 and 10 days) phage therapy to study the change in the gut microbiome via high-throughput 16S rDNA sequence analysis, which revealed no notable alterations in the gut microbiota except for decreases in the Chao1 and ACE indexes.